Nevanlinna Theory for the Uniqueness of Difference Polynomials and Meromorphic Functions by Sharing one Small Function (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The purpose of this paper is to extend the usual Nevanlinna theory to the periodic functions, difference operators and difference polynomials of meromorphic functions concerning their uniqueness after sharing one small function and satisfying certain conditions on the number of zeros and poles of the functions.